Inhibition of Propolis on the Growth of Aggregatibacter Actinomycetemcomitans: Daya Hambat Propolis terhadap Pertumbuhan Aggregatibacter Actinomycetemcomitans - Novita Pratiwi; Anis Khoirin Hayati; Nurul Maulidah (Academia Open, 2025)
General Background: Periodontitis, a chronic inflammatory disease, leads to tooth loss, with Aggregatibacter actinomycetemcomitans playing a key role in its pathogenesis. Specific Background: The rise of antibiotic resistance necessitates alternative treatments. Propolis, a bee-derived resin, has shown antimicrobial properties. Knowledge Gap: Limited research exists on the inhibitory effects of propolis against A. actinomycetemcomitans at varying concentrations. Aims: This study evaluates the antibacterial activity of propolis extract on A. actinomycetemcomitans in vitro. Results: Propolis exhibited significant antibacterial effects, with a minimum inhibitory concentration of 12.5% (125 mg/mL), attributed to flavonoids and apigenin. Statistical analysis confirmed significant differences across concentrations (p < 0.05). Novelty: This study highlights the concentration-dependent antibacterial efficacy of propolis against A. actinomycetemcomitans, suggesting its potential as a natural therapeutic. Implications: Propolis may serve as a complementary antimicrobial in periodontal therapy, reducing antibiotic reliance and resistance. Highlights: Effective Antibacterial Agent – Propolis inhibits A. actinomycetemcomitans growth at a minimum concentration of 12.5% (125 mg/mL). Bioactive Components – Flavonoids and apigenin in propolis disrupt bacterial membranes and biofilm formation. Clinical Potential – Propolis may serve as a natural alternative to antibiotics in periodontal therapy. Keywords: Periodontitist, Propolis, Aggregatibacter Actinomycetemcomitans, Antimicroba